Effect of quality of corporate disclosure and board characteristics on analysts' forecasts. - Lee, Miang Kear. (2008)
Our study aims to determine whether analysts’ earnings forecasts are associated to the quality of corporate disclosure and the board characteristics of U.S. companies. An important conclusion for this research is that board characteristics can add to and reinforce effects of quality of corporate disclosure to influence analysts’ forecasts.